Math, asked by sajidkhansla, 3 months ago

limit X approaches to zero x divided by 3-
 \sqrt{x + 9}

Answers

Answered by mathdude500
4

\large\underline{\sf{Solution-}}

\rm :\longmapsto\:\displaystyle\lim_{x \to 0}\rm \: \dfrac{x}{3 -  \sqrt{x + 9} }

On directly Substitute x = 0, we get

\rm \:  =  \:  \: \dfrac{0}{3 -  \sqrt{0 + 9} }

\rm \:  =  \:  \: \dfrac{0}{3 -  \sqrt{ 9} }

\rm \:  =  \:  \: \dfrac{0}{3 -  3}

\rm \:  =  \:  \: \dfrac{0}{0}

\rm \:  =  \:  \: which \: is \: meaningless

So, Consider again

\rm :\longmapsto\:\displaystyle\lim_{x \to 0}\rm \: \dfrac{x}{3 -  \sqrt{x + 9} }

\rm \:  =  \:  \: \:\displaystyle\lim_{x \to 0}\rm \: \dfrac{x}{3 -  \sqrt{x + 9} }  \times \dfrac{3 +  \sqrt{x + 9} }{3 +  \sqrt{x + 9} }

\rm \:  =  \:  \: \:\displaystyle\lim_{x \to 0}\rm \: \dfrac{x(3 +  \sqrt{x + 9} \: ) }{ {3}^{2}  - (x + 9)}

\rm \:  =  \:  \: \:\displaystyle\lim_{x \to 0}\rm \: \dfrac{x(3 +  \sqrt{x + 9} \: ) }{9 - (x + 9)}

\rm \:  =  \:  \: \:\displaystyle\lim_{x \to 0}\rm \: \dfrac{x(3 +  \sqrt{x + 9} \: ) }{9 - x  -  9}

\rm \:  =  \:  \: \:\displaystyle\lim_{x \to 0}\rm \: \dfrac{x(3 +  \sqrt{x + 9} \: ) }{ - x}

\rm \:  =  \:  \: \:\displaystyle\lim_{x \: \to  \: 0}\rm \: \dfrac{(3 +  \sqrt{x + 9} \: ) }{ - 1}

\rm \:  =  \:  \:  - (3 +  \sqrt{9 + 0} \: )

\rm \:  =  \:  \:  - (3 +  \sqrt{9} \: )

\rm \:  =  \:  \:  - (3 +  3 \: )

\rm \:  =  \:  \:  - 6

Hence,

\rm :\longmapsto\:\displaystyle\lim_{x \to 0}\bf \: \dfrac{x}{3 -  \sqrt{x + 9} }  =  -  \: 6

Additional Information :-

 \boxed{ \bf{ \displaystyle\lim_{x \to 0}\bf\: \dfrac{sinx}{x}  = 1}}

 \boxed{ \bf{ \displaystyle\lim_{x \to 0}\bf\: \dfrac{tanx}{x}  = 1}}

 \boxed{ \bf{ \displaystyle\lim_{x \to 0}\bf\: \dfrac{ {sin}^{ - 1} x}{x}  = 1}}

 \boxed{ \bf{ \displaystyle\lim_{x \to 0}\bf\: \dfrac{ {tan}^{ - 1} x}{x}  = 1}}

 \boxed{ \bf{ \displaystyle\lim_{x \to 0}\bf\: \dfrac{ log(1 + x) }{x} = 1 }}

 \boxed{ \bf{ \displaystyle\lim_{x \to 0}\bf\: \dfrac{ {e}^{x}  - 1}{x} = 1 }}

 \boxed{ \bf{ \displaystyle\lim_{x \to 0}\bf\: \dfrac{ {a}^{x}  - 1}{x} = loga }}

Similar questions